2009
DOI: 10.1093/carcin/bgp047
|View full text |Cite
|
Sign up to set email alerts
|

NDRG2 expression decreases with tumor stages and regulates TCF/ -catenin signaling in human colon carcinoma

Abstract: NDRG (N-Myc downstream-regulated gene)-2 is a member of the NDRG family. Although it has been suggested that NDRG2 is involved in cellular differentiation and tumor suppression, its intracellular signal and regulatory mechanism are not well known. Here, we show the differential expression of NDRG2 in human colon carcinoma cell lines and tissues by reverse transcriptionpolymerase chain reaction and immunohistochemical analyses with monoclonal antibody against NDRG2. NDRG2 was strongly expressed in normal coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 35 publications
5
69
0
Order By: Relevance
“…Of note, the closely related NDRG family member NDRG2, has been demonstrated to function as a tumor suppressor through its effects on b-catenin (Kim et al, 2009;Hwang et al, 2011). However, in marked contrast to NDRG1, NDRG2 interacts with b-catenin through its a6 helix residue L172 (Hwang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the closely related NDRG family member NDRG2, has been demonstrated to function as a tumor suppressor through its effects on b-catenin (Kim et al, 2009;Hwang et al, 2011). However, in marked contrast to NDRG1, NDRG2 interacts with b-catenin through its a6 helix residue L172 (Hwang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that NDRG2 could suppress cell proliferation through the regulation of cyclin D1 and TCF/b-catenin activity (19,20). NDRG2 was also reported to suppress NF-kB activity in order to inhibit carcinogenesis, invasion, and metastasis of human malignancy (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that aberrant expression of NDRG2 in malignancy could serve as a tumor-suppressive role in carcinogenesis. Moreover, it is reported that NDRG2 could suppress cell proliferation possibly through the regulation of cyclin D1 and T-cell factor (TCF)/b-catenin activity (19,20). Recent study also showed that NDRG2 could suppress nuclear factor kappa B (NF-kB) activity, suggesting a possible mechanism for NDRG2 to participate in carcinogenesis and progression of human malignancy (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Just as NDRG2 expression levels are reduced in GBM, decreased NDRG2 expression is observed in colorectal adenocarcinoma (40,41), and thyroid (42), hepatocellular (43), gastric (44), and clear cell renal (45) carcinomas. Consistent with these expression patterns, NDRG2 has been reported to suppress cellular proliferation (44,46), suppress invasion and metastasis (43), and be required for apoptotic pathways including Fasmediated cell death (44) and p53-mediated apoptosis (47).…”
Section: Discussionmentioning
confidence: 99%